4‐Phenyl‐3‐thiosemicarbazide Modified Magnetic Nanoparticles: Synthesis, Characterization and Application for Heavy Metal Removal. Issue 9 (10th March 2014) - Zargoosh, Kiomars; Zilouei, Hamid; Mohammadi, Mohammad Reza; Abedini, Hamed
<x xml:space="preserve">Abstract</x> A novel magnetic nano‐adsorbent has been synthesized by the covalent immobilization of poly (acrylic acid) (PAA) and a ligating agent 4‐phenyl‐3‐thiosemicarbazide (TSC) on the surface of Fe3O4 nanoparticles. The prepared magnetic nanoparticles (MNPs) were characterized by scanning electron microscopy (SEM), atomic force microscopy, vibrating sample magnetometer, Fourier transform infrared spectroscopy and X‐ray diffraction analysis. The SEM images showed that the diameters of the Fe3O4@PAA@TSC MNPs are about 40–60 nm. The ability of the Fe3O4@PAA@TSC MNPs for removing heavy metal ions (Pb2+, Cd2+, Cu2+, Zn2+, and Co2+) from aqueous solution was studied and the effects of the pH, contact time, metal ion concentration, and background electrolytes on the adsorption characteristics of the modified MNPs were investigated. The maximum adsorption capacity of Pb2+, Cd2+, Co2+, Cu2+, and Zn2+ were found to be 181.1, 125.0, 86.2, 67.1, and 57.8 mg g−1, respectively. Excellent adsorption capacity of the modified nano‐adsorbent together with other advantages such as reusability, easy synthesis, easy separation and more specially freedom of interferences of alkaline earth metal ions make them suitable alternatives to the well‐known adsorbents for removal of heavy metal ions from industrial wastes.